LATENT NUCLEAR TRACKS OR NANOPOROUS RODS: DEFECT STRUCTURE AND DAMAGE REPAIR DURING ANNEALING *M. - Rana, M. A. (The Nucleus, 2020)
Experimental results on the subject of defect structure of latent nuclear tracks and their damage repair during annealing in a track detector CR-39 are presented. These results suggest that latent nuclear tracks can be considered as nanoporous rods with nanometre scale pores along the central axis of the cylindrical track. An overview of a model about repair of radiation damage in solids is given. Model calculations are compared with experimental results regarding repair of nuclear track damage in CR-39. A convincing agreement is found between experimental results and model calculations. Results and discussion presented here are useful for better interpretation of results from nuclear geology and cosmic-ray physics experiments.